Protection of the Rights of Children Affected by the Intra-Eu Migration in the Danube Region - Koev, Krasimir; Popova, Ana (Journal of Danubian Studies and Research, 2023)
Objectives: The aim of this paper is to interpret the issues of internal migration in the EU with a focus on the children affected by the processes of labor migration. The internal migration within the EU, caused by leaving the home country for a certain period of time in search of better income or work, is a phenomenon that is typical for all Eastern European countries, including some of the Danube countries, in the period of democratic changes and social macro-transformation. Regardless of whether the children in the family accompany their parents abroad during the labor migration or they are left in the home country in the care of relatives and friends, these children have their basic rights violated under the UN Convention on the Rights of the Child, for example the right of education and healthcare. Prior Work: Theoretical and experimental research of the authors in the field. Approach: Secondary data analysis of existing statistics and analysis of authorship in-depth interviews with the representatives of the target group. Results: The labour migration affects almost 20 % of the children from so called transnational families living in the countries from the Danube region. It causes deficits in their socialisation and risks for their physical, emotional and cognitive development. The labor migration of the parents of such children is not also in compliance of the basic rights of the children from migrant families: right of healthcare, right of education, etc. Implications: The paper can stimulate a larger discussion in the scientific circles about the necessity of joint research on the protection of the rights of the children from migrant families. Value: The study identifies some institutional strategies that can prevent the violation of the rights of the children from migrant families.